1983
DOI: 10.1021/jo00174a013
|View full text |Cite
|
Sign up to set email alerts
|

Chelation control of enolate geometry. Acyclic diastereoselection via the enolate Claisen rearrangement

Abstract: Appropriate fractions are combined and concentrated. The product is dried in a desiccator under vacuum. The yield is less than 0.05 g. The 13C NMR spectrum is identical with that of unenriched dipalmitoyl-PC (Figure 2b) except for the intensities of the downfield carbonyl resonances.The latter are discussed in Results and Discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…Alternatively LDA was used, but neither method worked (entries 3, 5, 7, and 10). Finally, a protocol by Burke was employed, 25 which he had been successfully applied to a Claisen substrate carrying an enone moiety in a similar fashion as compared to 20c (entries 8 and 9). Even this method failed.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively LDA was used, but neither method worked (entries 3, 5, 7, and 10). Finally, a protocol by Burke was employed, 25 which he had been successfully applied to a Claisen substrate carrying an enone moiety in a similar fashion as compared to 20c (entries 8 and 9). Even this method failed.…”
Section: Resultsmentioning
confidence: 99%
“…Burke has demonstrated that silyl ketene acetals of O ‐benzylglycolates rearrange to give a 91:9 mixture of diastereomers (Scheme ) 23. Since the enolization of these esters is controlled geometrically by chelation, this work suggests that silyl ketene acetals of these substrates prefer to rearrange through chair versus boat transition states in an equivalent ratio.…”
Section: Resultsmentioning
confidence: 79%
“…Stereoselective reduction of 144 gave alcohol 145 as a single isomer, which was esterified with PMBOCH 2 COOH under Mitsunobu conditions to provide the protected glycolate ester 146 in 92% yield. Chelation controlled glycolate enolate Claisen rearrangement [53] led to acid 147 as single isomer in 98% yield. Formation of the methyl ester followed by DIBAL reduction afforded aldehyde 148, which was subjected to the Still-Gennari olefination.…”
Section: Synthesis Of Branimycinmentioning
confidence: 99%